2014 IEEE Vehicle Power and Propulsion Conference (VPPC) 2014
DOI: 10.1109/vppc.2014.7007085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PWM Strategies on RMS Current of the DC-Link Voltage Capacitor of a Dual-Three Phase Drive

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Inverter (VSI), is the occurrence of extra harmonic currents which circulate in the stator windings causing additional losses and constraints on the power component. This paper compares dedicated Pulse Width Modulation (PWM) strategies used for controlling a dual threephase Permanent Magnet Synchronous machine supplied by a six-leg VSI. Since the application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Further assuming that the DC source supplies the entire DC component of the DC link current and the DC link capacitor provides the entire AC component, (9) and (10) show the DC link capacitor current results.…”
Section: Fig 10 Simulation Results Mcpwmd: I Crms Locus Of the Greamentioning
confidence: 99%
See 1 more Smart Citation
“…Further assuming that the DC source supplies the entire DC component of the DC link current and the DC link capacitor provides the entire AC component, (9) and (10) show the DC link capacitor current results.…”
Section: Fig 10 Simulation Results Mcpwmd: I Crms Locus Of the Greamentioning
confidence: 99%
“…In the past, different methods to reduce the DC link and RMS current have been presented [2,[6][7][8][9]. In general, the DC link RMS current decreases as the number of phases increase [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the interaction between current and voltage components of the same sequence, and due to the existence of only first positive and zero sequence load voltage components, only current components I +1 and I −1 contribute to the instantaneous power. Introducing Equations ( 20) and (21) in Equation ( 19), the instantaneous power becomes…”
Section: Dc-link Low-frequency Current and Voltage Ripple Analysis In...mentioning
confidence: 99%
“…For example, in [14] the impact of classical PWM modulation, with and without common mode injection on the RMS value of the dc-link current has been studied for dual-three phase induction machine. A PWM strategy dedicated to minimization of the RMS of the dc-link current in dual three-phase drive has been compared in [15] with more conventional PWM techniques. It has been shown that PWM strategies have different effect on the RMS of the dc-link current and on the quality of the output current.…”
Section: Introductionmentioning
confidence: 99%